The effect of internet-based intervention (obeseGO!) towards obesity among adolescents: A randomized controlled trial study - Che Jamaludin, Farrah Ilyani; Mohammed Nawi, Azmawati; Che Hasan, Muhammad Kamil (2014)
Obesity in adolescents is a significant problem which is associated with co-morbidities in adulthood. Other than unhealthy diet, sedentary lifestyle, and spending more time on screen are among the causes contributing to obesity. The internet may be an effective means of reaching adolescents in promoting them to increase exercise and improve nutrition habits, leading to weight loss and control. This 3 month randomized controlled trial was aim to see the effectiveness of having internet-based intervention (obeseGO!) towards obesity among adolescents in Kuala Lumpur. Forty seven students were randomly allocated in obeseGO! Group and signed up to actively participate in the internet based intervention. They were given various information on healthy lifestyle and diet via internet. Fifty students were served as a control group and they were given health education via pamphlet. Measurement of BMI, waist circumference and body fat percentage was taken at baseline and after 12 weeks of intervention given. MANCOVA analysis found that obeseGO! is effective in reducing BMI (mean diff. =-0.39, CI;-0.59, -0.20, p<0.001), waist circumference (mean diff.= -1.19, CI; -1.89, -0.50, p= 0.001) and body fat percentage (mean diff.= -0.59, CI; -0.93, -0.24, p=0.001) when the possible confounder such gender, race, physical activity level, the pre measurement of BMI, Waist Circumference and Body Fat Percentage were controlled. Internet-based obesity intervention program may be an effective medium for promoting healthy diet and physical activity behavior in obese adolescents.